2022
DOI: 10.3390/diagnostics12020493
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and Clinical Parameters for Distinction between Infected and Non-Infected Fluid Collections in CT: Prospective Study Using Extended Microbiological Approach

Abstract: The aim of this investigation was to evaluate predictive CT imaging features and clinical parameters to distinguish infected from sterile fluid collections. Detection of infectious agents by advanced microbiological analysis was used as the reference standard. From April 2018 to October 2019, all patients undergoing CT-guided drainages were prospectively enrolled, if drainage material volume was at least 5 mL. Univariate analysis revealed attenuation (p = 0.001), entrapped gas (p < 0.001), fat stranding (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…However, the quantitative measurements of the spectral reconstructions were not superior compared with measurements in conventional images 30 There is definite need to further evaluate the possible benefit of texture analysis derived from dual-energy CT. Other authors elucidated the diagnostic benefit of HUs or clinical scores with mixed results. 31,32 The present study corroborates the abovementioned findings that texture analysis might aid to diagnose the etiology of fluid collections in a non-invasive and time efficient manner. However, the diagnostic overlap identified in the present study is relative large, which could reduce the benefit for clinical routine.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the quantitative measurements of the spectral reconstructions were not superior compared with measurements in conventional images 30 There is definite need to further evaluate the possible benefit of texture analysis derived from dual-energy CT. Other authors elucidated the diagnostic benefit of HUs or clinical scores with mixed results. 31,32 The present study corroborates the abovementioned findings that texture analysis might aid to diagnose the etiology of fluid collections in a non-invasive and time efficient manner. However, the diagnostic overlap identified in the present study is relative large, which could reduce the benefit for clinical routine.…”
Section: Discussionsupporting
confidence: 90%
“…The conclusions drawn of this study were that spectral reconstructions could improve the assessment of infected fluid collections and the help to depict the wall enhancement. However, the quantitative measurements of the spectral reconstructions were not superior compared with measurements in conventional images 30 There is definite need to further evaluate the possible benefit of texture analysis derived from dual-energy CT. Other authors elucidated the diagnostic benefit of HUs or clinical scores with mixed results 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…In the presented case the CT scan revealed two small fluid collections and contrast media recess within the internal jugular vein. These findings previously undectected by clinical and endoscopic examinations in this case represent typical abscess formations and internal jugular vein thrombosis in Lemierre's syndrome [9] and led to the final diagnosis. Thus, only the combination of patient's history, highly elevated PCT levels and CT scan findings allowed for the detection of systemic infection and correct diagnosis of severe bacteremia in this case.…”
Section: Discussionsupporting
confidence: 62%
“…Another recent prospective study assessed the role of CT imaging in the differential identification of an infected area at a sterile body site. The results of this study revealed that CT imaging features demonstrating attenuation >10 Hounsfield units (HU), entrapped gas, and wall enhancement could indicate the presence of microbial infection [ 11 ]. Tc-leukocyte scintigraphy was applied to a patient with recurrent spikes of fever.…”
Section: Reviewmentioning
confidence: 99%